GDF11 Implications in Cancer Biology and Metabolism. Facts and Controversies - Simoni-Nieves, Arturo; Gerardo-Ramírez, Monserrat; Pedraza-Vázquez, Gibrán; Chávez-Rodríguez, Lisette; Bucio, Leticia; Souza, Verónica; Miranda-Labra, Roxana U.; Gomez-Quiroz, Luis E.; Gutiérrez-Ruiz, María Concepción (Frontiers in Oncology, 2019)
Growth Differentiation Factor 11 (GDF11) a member of the super family of the Transforming Growth Factor β, has gained more attention in the last years due to numerous reports regarding its functions in other systems different to those related to differentiation and embryonic development, such as age-related muscle dysfunction, skin biology, metabolism and cancer. GDF11 is expressed in many tissues including skeletal muscle, pancreas, kidney, nervous system, and retina, among others. GDF11 circulating levels and protein content in tissue is quite variable and is affected by pathological conditions or age. Although, GDF11 is covered by many controversies, we believe that must of them are only misunderstandings regarding the variability of its responses, which are dependent of the tissue, grade of cellular differentiation or pathologies. One of the clear facts, regarding GDF11 biology is that it targets cells with stemness feature, property that could be found in certain adult cells in health and in the disease, such as cancer cells. This review is focused to present and analyze the recent findings in the emerging research field of GDF11 function in cancer and metabolism, and discuss the controversies surrounding the biology of this atypical growth factor.